The effects of family communication and parental school support on delinquent behaviors: an analysis of gender and ethnic factors - Davalos, Deana, author; Chavez, Ernest L., advisor; Boyer, William N., committee member; Turner, Ronny A., committee member; Bloom, Larry J., committee member (Colorado State University. Libraries, 2000)
This study examined variables associated with delinquency and sexual behavior in Latino and White non-Hispanic adolescents. Family relationship variables that were surveyed included the participants' perceived level of family communication and parental school support. Data analysis included investigation of the above stated variables, sexual behavior, and the relationship to gender and ethnicity. Results demonstrated that both family communication and parental school support were related to the likelihood of committing delinquent acts. There did not appear to be significant differences regarding males and females in the levels of family communication and parental school support. Regarding sexual behavior, on many measures there were no significant differences between males and females or White non-Hispanics and Latinos. There did appear to be differences in the age of initiation of sexual behavior, number of partners, and particular sexual acts. Future research may ascertain which types of interventions may be most effective regarding ethnicity and gender.
Keywords: social psychology; developmental psychology; behavioral sciences; families and family life; personal relationships; sociology; minority and ethnic groups